Macrophage roles in the clearance of apoptotic cells and control of inflammation in the prostate gland after castration. Issue 2 (14th November 2017) - Silva, Juliete A.F.; Bruni‐Cardoso, Alexandre; Augusto, Taize M.; Damas‐Souza, Danilo M.; Barbosa, Guilherme O.; Felisbino, Sérgio L.; Stach‐Machado, Dagmar R.; Carvalho, Hernandes F.
Abstract : Background: Androgen deprivation results in massive apoptosis in the prostate gland. Macrophages are actively engaged in phagocytosing epithelial cell corpses. However, it is unknown whether microtubule‐associated protein 1 light chain 3 alpha (LC3)‐associated phagocytosis (LAP) is involved and contribute to prevent inflammation. Methods: Flow cytometry, RT‐PCR and immunohistochemistry were used to characterize the macrophage subpopulation residing in the epithelial layer of the rat ventral prostate (VP) after castration. Stereology was employed to determine variations in the number of ED1 and ED2. Mice were treated with either chloroquine or L‐asparagine to block autophagy. Results: M1 (iNOS‐positive) and M2 macrophages (MRC1+ and ARG1+) were not found in the epithelium at day 5 after castration. The percentage of CD68 + (ED1) and CD163 + (ED2) phenotypes increased after castration but only CD68 + cells were present in the epithelium. RT‐PCR showed increased content of the autophagy markers Bcl1 and LC3 after castration. In addition, immunohistochemistry showed the presence of LC3 + and ATG5 + cells in the epithelium. Double immunohistochemistry showed these cells to be CD68 + /LC3 +, compatible with the LAP phenotype. LC3 + cells accumulate significantly after castration. Chloroquine and L‐asparagine administration caused inflammation of the glands at day 5 after castration. Conclusions: CD68 + macrophages phagocytose apoptotic cell corpses and activate the LAP pathway, thereby contributing to the preservation of a non‐inflammed microenvironment. Marked inflammation was detected when autophagy blockers were administered to castrated animals.